Lichens as a spatial record of metal air pollution in the industrialized city of Huelva (SW Spain). (October 2019) - Parviainen, Annika; Casares-Porcel, Manuel; Marchesi, Claudio; Garrido, Carlos J.
Abstract: Huelva is a highly industrialized city in SW Spain hosting, among others, a Cu smelter, a phosphate fertilizer plant, a power plant, and oil refineries. This study aims to evaluate metal concentrations in lichens as bioindicators of atmospheric pollution in the impacted urban areas. Xanthoria parietina species from Huelva and nearby villages, as well as reference samples from remote, non-contaminated urban areas, were analyzed for trace elements (V, Cr, Mn, Co, Ni, Cu, Zn, Sr, As, Cd, Sb, Cs, Ba, La, Ce, Pr, Nd, Sm, Er, Tm, Yb, Lu, Pb, Th, U) using Inductively Coupled Plasma-Mass Spectrometry; and for major elements (Ca, K, Mg, P, and S) by Inductively Coupled Plasma-Optical Emission Spectrometry after acid digestion. The metal composition of X. parietina exhibits spatial distribution patterns with extremely elevated concentrations (Co, Ni, Cu, Zn, As, Cd, Sb, Ba, Pb, U, and S) in the surroundings of the industrial estates to <1 km distance. Mean concentrations were significantly lower in the urban areas >1 km from the pollution sources. However, air pollution persists in the urban areas up to 4 km away, as the mean concentrations of Cu, Zn, As, Cd, Sb and S remained considerably elevated in comparison to the reference samples. Though rigorous source apportionment analysis was not the aim of this study, a good positive correlation of our results with metal abundances in ambient particulate matter and in pollution sources points to the Cu smelter as the main source of pollution. Hence, the severe air pollution affecting Huelva and nearby urban areas may be considered a serious health risk to local residents. Graphical abstract: Image 1 Highlights: Epiphytic lichens were used as bioindicators of metal air pollution in Huelva (Spain). Lichens exhibit spatial metal distribution over nearby urban areas. Elevated concentrations of Co, Ni, Cu, Zn, As, Cd, Sb, Ba, Pb, U, and S were gauged. Metal pollution derives from industrial activities, especially from Cu smelting. Metal air pollution may pose a health risk to residents. Abstract : Extreme concentrations of potentially toxic elements in lichens in urban areas surrounding industrial estates imply severe air pollution and a potential health risk to residents.